The Preparation of Silk Fibroin Drug-loading Microspheres (Journal of Fiber Bioengineering and Informatics, 2018)
This paper deals with the development of a kind of water-in-oil-in-water (w/o/w)multiple-emulsification method to fabricate the SF drug-loading microspheres. The silk fibroin (SF)microspheres were prepared by using SF as vehicle and dexamethasone sodium phosphate (DSP) asdrug model. The surface morphology was observed by SEM, the particle diameter and its distributionwere observed with Laser particle sizer. The structure was studied by X-ray diffraction and Fouriertransform infrared. The properties of drug release were assessed in vitro. The results showed the averagesize of microspheres varied from 6.53 &#956m to 68.60 &#956m. The structure of SF drug-loading microsphereshad an obviously change compared with pure SF; and the change is the appearance of silk I and silkII structures; and its molecular conformation was &#946-sheet. The average drug-loading varied from 5.32% to 9.01 %, and the average loading varied from 56.43 % to 99.07 %. The drug-loading and loadingefficiency increased with the increase of SF concentration. The drug-loading and loading efficiencydiffered when the treated organic solvent differed, their order is: isopropanol &#8249 acetone &#8249 ethanol. Drugrelease of SF drug-loading microspheres: there was a slow release effect when the concentration of SFwas 3% or 6%. Moreover, in the experimental condition, there was an obvious burst release of the drugwhen the SF concentration was 9 % or 12 % or when the treated solvent was ethanol.